Effects of Temperature and Layer Thicknesses on Drying Kinetics of Coconut Residue - Assawarachan, Rittichai (วารสารสมาคมวิศวกรรมเกษตรแห่งประเทศไทย, 2016)
In this study, coconut residue were dried as single layers with thickness of 7.5, 10, and 12.5 mm in drying air temperatures of 55, 65 and 75°C in a laboratory scale tray dryer. The effect of drying air temperature and thickness on the drying characteristics was determined. A non-linear regression procedure was used to fit experimental moisture loss data using three empirical models, namely, Newton, Henderson and Pabis, and Page. The Page model showed an excellent fit to predict drying behavior of the coconut residue because this model gave the highest coefficient of determination (R2) and the lowest chi-square (c2) and root mean square error (RMSE).The 3-D response surface plot and the contour plot derived from the mathematical models were applied to determine drying parameter prediction equations.The Response surface analysis (3-D) showing the effect of temperature (°C) and layer thickness (L) on the response in the change in drying rate (k) and drying index (n) of Page model during hot air drying, was found to be in close agreement with the value predicted by the model. Moisture transfer from coconut residue was described by applying the Fick’s diffusion model, and the effective diffusivity (Deff) changes between 0.99-4.17x10 -10 m2 s-1 and the activation energy of moisture diffusion during drying was found to be 12.04 to 44.22 kJ mol -1